2021
DOI: 10.11606/issn.1678-4456.bjvras.2021.178023
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids profile, atherogenic and thrombogenic health lipid indices in the meat of lambs that received canola grain

Abstract: This study evaluated the fatty acid composition and qualitative characteristics of meat from lambs feed in feedlot with increasing levels of canola grain. Meat obtained from 27 lambs fed 0, 8 and 16% inclusion of canola grain were analyzed. There was a reduction in the content of saturated fatty acids (SFA): lauric, heptadecanoic, and stearic; and unsaturated fatty acids (UFA): palmitoleic, oleic, and eicosatrienoic, with the increasing levels of canola grain. There was a linear reduction for the ω3 acid and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
5
6
0
Order By: Relevance
“…The sums of SFAs were found to be decreased to be closer to the recommended value by the USDA (30.6%) as reported by De . These results, which are in agreement with Carneiro et al (2021), Osuna et al (2018), De Souto et al (2021 and Singh et al (2011), should be convenient since developing products with low SFAs content is one of the aims of the food industry technologists.…”
Section: Fatty Acid Profilesupporting
confidence: 83%
See 1 more Smart Citation
“…The sums of SFAs were found to be decreased to be closer to the recommended value by the USDA (30.6%) as reported by De . These results, which are in agreement with Carneiro et al (2021), Osuna et al (2018), De Souto et al (2021 and Singh et al (2011), should be convenient since developing products with low SFAs content is one of the aims of the food industry technologists.…”
Section: Fatty Acid Profilesupporting
confidence: 83%
“…Myristic acid (C14:0) content was found to be decreased after the addition of the oils. This cannot be preferable since Carneiro et al (2021) revealed that this fatty acid is attributed to the increased LDL in blood serum that is responsible for hypercholesterolemia; which causes cardiovascular disease, sequelae, and arteriosclerosis.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…There are no recommended values for IT and IA, although lower values indicate a more promising fatty acid ratio for human health promotion. Consequently, a meat with low IT and IA values might be considered of better nutritional quality for humans, as it presents a higher amount of anti-atherogenic fatty acids than meats with high ratios, possibly contributing to coronary heart disease prevention [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated the advantageous reducing effects of SAG, PIN, and CLO at specific dose levels on the in vitro concentrations of C14:0 and C16:0. The saturated fatty acids, particularly C14:0 and C16:0, have been extensively studied and are known to possess atherogenic and thrombogenic properties, as documented by Carneiro et al [60]. Notably, various studies, including those by Al-Amiri et al [61] and Praagman et al [62], have consistently reported their ability to elevate cholesterol levels and promote platelet aggregation.…”
Section: In Vitro Biohydrogenation and Fatty Acid Concentrationsmentioning
confidence: 98%